L2pB1 Cells Contribute to Tumor Growth Inhibition - Shibad, Varuna; Bootwala, Ali; Mao, Changchuin; Bader, Hanna; Vo, Hung; Landesman-Bollag, Esther; Guo, Conrad; Rubio, Angel; Near, Richard; Gao, Wenda; Challa, Sreekar; Chukka, Vennela; et al. (Frontiers in Immunology, 2021)
Natural IgM (nIgM) antibodies play critical roles in cancer immunosurveillance. However, the role of B-1 B cells, the lymphocytes that produce nIgM, remains to be elucidated. L2pB1 cells, a subpopulation of B-1 B cells, have a unique poly-self-reactive nIgM repertoire and are capable of phagocytosis, potent antigen presentation, and immunomodulation. Using an inducible knock-in and knockout mouse model, we investigated the effect of the loss of L2pB1 cells in a B16F10 melanoma model. Our results show active tumor infiltration of L2pB1 cells in wild type mice, and conversely, depletion of L2pB1 cells results in larger tumor mass and increased angiogenesis. In vitro analysis revealed that L2pB1 cells contribute to the growth inhibition of melanoma cells in both 2D cell culture and 3D tumor spheroids. Similar effects were observed in an MC38 murine colon cancer model. Moreover, our data suggest that one of the ways that L2pB1 cells can induce tumor cell death is via lipoptosis. Lastly, we tested whether L2pB1 cell-derived monoclonal nIgM antibodies can specifically recognize tumor spheroids. Nine of the 28 nIgM-secreting L2pB1 clones demonstrated specific binding to tumor spheroids but did not bind control murine embryonic fibroblasts. Our study provides evidence that L2pB1 cells contribute to cancer immunity through their unique nIgM repertoire, tumor recognition, and lipoptosis. Taken together, because of their ability to recognize common features of tumors that are independent of genetic mutations, L2pB1 cells and their nIgM could be potential candidates for cancer treatment that can overcome tumor heterogeneity-associated drug resistance.